HUBUNGAN JENIS POLA ASUH ORANG TUA DENGAN KEJADIAN SIBLING RIVALRY PADA ANAK USIA 3-12 TAHUN DI DESA JOHO KECAMATAN PACE KABUPATEN NGANJUK - YESY NUR YAERINA, NIM011211231001 (2016)
Pattern foster parent is one of the factors that influence the incidence of sibling rivalry in children aged 3-12 years. A total of 64.3% of children had sibling rivalry. The purpose of this research is to study the influence of parents' parenting on the incidence of sibling rivalry in children aged 3-12 years in Desa Joho District of Pace Nganjuk. This study uses observational analytic with cross sectional approach in March- April 2016. The respondents were parents and children aged 3-12 years in accordance with the terms of inclusion and exclusion. The number of samples with a total sampling as many as 42 parents and children aged 3-12 years. The independent variables studied were parenting parents while the dependent variable was the incidence of sibling rivalry in children aged 3-12 years. Collecting data are using questionnaires. Analysis using Chi-square test (χ2) with α = 0.05. The results showed the authoritarian parenting 31.0%, 31.0% democratic, and permissive 11.8% and 26.2% passive. Most children at the age of 3-12 years’ experience sibling rivalry as much as 27 events (64.3%) children who are not as much as 15 (35.7%) children. Type of parenting has a significant relationship to the incidence of sibling rivalry in children aged 3-12 years. The result of the analysis showed the value of p = 0.000 (p ≤ 0.05), with the value of contingency coefficient of 0.651, which means Ho is rejected and H1 accepted, which means having a strong relationship. The conclusion of this study is a significant relationship between the type of parenting parents on the incidence of sibling rivalry in children aged 3-12 years where the application of appropriate parenting on children is very important to prevent the incidence of sibling rivalry in the family in the village of Joho District of Pace Nganjuk